Peran Pendidikan Dalam Menguatkan Moderasi Beragama dan Toleransi - Sani Yulianti; Rita Rostiani; Tetep Tetep; Jamilah Jamilah (Penerbit Widina, Widina Media Utama, 2026)
Indonesia is a country with a very high level of religious, ethnic, cultural, linguistic, and customary diversity, which is both a strength and a challenge in the life of the nation and state, especially when various phenomena of intolerance, hate speech, and religious-based conflicts are still encountered, indicating that the values of tolerance and respect for differences have not been fully internalized in society. Therefore, religious moderation is an important concept to be developed as an effort to maintain social harmony amidst the nation's plurality. Education is seen as a strategic instrument in strengthening religious moderation and fostering an attitude of tolerance because it not only functions as a means of transferring knowledge, but also plays a role in shaping the character, attitudes, and perspectives of students so that they have an inclusive and moderate religious understanding. This study aims to examine the role of education in strengthening religious moderation and fostering an attitude of tolerance amidst the diversity of Indonesian society using a qualitative approach through a literature study of relevant national and international academic books and scientific journal articles, especially those published in the last ten years. Data were analyzed using qualitative content analysis techniques to identify the main concepts, ideas, and findings of experts. The results of the study indicate that education has a strategic role in internalizing the value of religious moderation through the development of an inclusive curriculum, the application of dialogic and participatory learning methods, the role model of educators, and the creation of a school culture that respects diversity, where multicultural-based education has proven effective in strengthening attitudes of tolerance and awareness of peaceful coexistence, although its implementation still faces challenges in the form of narrow religious understanding, limited integration of the value of moderation in the curriculum, and the negative influence of social media, so that strengthening religious moderation through education needs to be carried out comprehensively and sustainably in order to form a tolerant, just, and civilized generation in a pluralistic Indonesian society.ABSTRAKIndonesia merupakan negara dengan tingkat keberagaman agama, suku, budaya, bahasa, dan adat istiadat yang sangat tinggi, yang menjadi kekuatan sekaligus tantangan dalam kehidupan berbangsa dan bernegara, terutama ketika masih dijumpai berbagai fenomena intoleransi, ujaran kebencian, dan konflik berbasis agama yang menunjukkan bahwa nilai toleransi dan penghargaan terhadap perbedaan belum sepenuhnya terinternalisasi dalam kehidupan masyarakat. Oleh karena itu, moderasi beragama menjadi konsep penting untuk dikembangkan sebagai upaya menjaga keharmonisan sosial di tengah pluralitas bangsa. Pendidikan dipandang sebagai instrumen strategis dalam menguatkan moderasi beragama dan menumbuhkan sikap toleransi karena tidak hanya berfungsi sebagai sarana transfer pengetahuan, tetapi juga berperan dalam pembentukan karakter, sikap, dan cara pandang peserta didik agar memiliki pemahaman keagamaan yang inklusif dan moderat. Penelitian ini bertujuan untuk mengkaji peran pendidikan dalam menguatkan moderasi beragama dan menumbuhkan sikap toleransi di tengah keberagaman masyarakat Indonesia dengan menggunakan pendekatan kualitatif melalui studi literatur terhadap buku akademik dan artikel jurnal ilmiah nasional maupun internasional yang relevan, khususnya yang terbit dalam sepuluh tahun terakhir. Data dianalisis menggunakan teknik analisis isi (content analysis) secara kualitatif untuk mengidentifikasi konsep, gagasan, dan temuan utama para ahli. Hasil kajian menunjukkan bahwa pendidikan memiliki peran strategis dalam menginternalisasikan nilai moderasi beragama melalui pengembangan kurikulum yang inklusif, penerapan metode pembelajaran yang dialogis dan partisipatif, keteladanan pendidik, serta penciptaan budaya sekolah yang menghargai keberagaman, di mana pendidikan berbasis multikultural terbukti efektif dalam memperkuat sikap toleransi dan kesadaran hidup berdampingan secara damai, meskipun implementasinya masih menghadapi tantangan berupa pemahaman keagamaan yang sempit, keterbatasan integrasi nilai moderasi dalam kurikulum, serta pengaruh negatif media sosial, sehingga penguatan moderasi beragama melalui pendidikan perlu dilakukan secara komprehensif dan berkelanjutan guna membentuk generasi yang toleran, adil, dan berkeadaban dalam masyarakat Indonesia yang majemuk.